2010
DOI: 10.1002/ibd.21085
|View full text |Cite
|
Sign up to set email alerts
|

Value of fractional exhaled nitric oxide (FENO) for the diagnosis of pulmonary involvement due to inflammatory bowel disease

Abstract: This study showed that an increased FE(NO) level may be used for identifying patients with IBD who need further pulmonary evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
0
33
2
3
Order By: Relevance
“…The Authors found high levels of FeNO in CD patients, and established a negative correlation between CDA and pulmonary function indexes (forced expiratory volume in one second and forced vital capacity), and went on to suggest the presence of a link between bronchial inflammation and systemic disease activity in CD. Another recent study by Ozyilmaz et al confirmed the correlation between FeNO levels and disease activity in patients with CD and ulcerative colitis (UC) (23). While these studies only considered FeNO levels (measured at 50 mils), and only contemplated one single exam per patient, the current study analyses eNO with multiple flow rates and at different stages of each patient's clinical and treatment courses.…”
Section: Discussionmentioning
confidence: 83%
“…The Authors found high levels of FeNO in CD patients, and established a negative correlation between CDA and pulmonary function indexes (forced expiratory volume in one second and forced vital capacity), and went on to suggest the presence of a link between bronchial inflammation and systemic disease activity in CD. Another recent study by Ozyilmaz et al confirmed the correlation between FeNO levels and disease activity in patients with CD and ulcerative colitis (UC) (23). While these studies only considered FeNO levels (measured at 50 mils), and only contemplated one single exam per patient, the current study analyses eNO with multiple flow rates and at different stages of each patient's clinical and treatment courses.…”
Section: Discussionmentioning
confidence: 83%
“…This parameter is considered to be a marker of airway inflammation. At least three independent authors found increased eNO in IBD patients compared to control subjects [37][38][39].…”
Section: Epidemiologymentioning
confidence: 99%
“…Bronchial hyperresponsiveness on methacholine challenge was independent of activity, extent and time of duration of IBD [29][30][31]. Exhaled NO correlated positively with IBD activity [37][38][39], but no relation was found for alveolar epithelial per-meability measured with the use of Tc-99m DTPA aerosol scintigraphy [40,41]. Data on relationship between IBD activity and chest HRCT picture are discrepant.…”
Section: Respiratory Disease Depending On Ibd Activitymentioning
confidence: 99%
“…The lung pathology, related to the use of these medicines includes interstitial disease [20][21][22][23], eosinophilic pleuritis [24], eosinophilic pneumonia [25][26][27], and bronchiolitis obliterans [28]. Biological therapy, with anti-TNF drugs such as infliximab, adalimumab and certolizumab, has been associated with several opportunistic infections, as a result of suppression of Tcell-mediated immunity, the most frequent being tuberculosis [29,30].…”
Section: Drug Side-effects To the Lungsmentioning
confidence: 99%